Continuous wound infiltration versus epidural analgesia for midline abdominal incisions - a randomized-controlled pilot trial (Painless-Pilot trial; DRKS number: DRKS00008023) - Klotz, Rosa; Seide, Svenja; Knebel, Phillip; Probst, Pascal; Bruckner, Thomas; Motsch, Johann; Hyhlik-Dürr, Alexander; Böckler, Dittmar; Larmann, Jan; Diener, Markus K.; Weigand, Markus A.; Büchler, Markus W.; et al. (PLOS ONE, 2020)
Objectives: To test the feasibility of a randomized controlled study design comparing epidural analgesia (EDA) with continuous wound infiltration (CWI) in respect to postoperative complications and mobility to design a future multicentre randomized controlled trial. Design, setting, participants: CWI has been developed to address drawbacks of EDA. Previous studies have established the equivalent analgesic potential of CWI compared to EDA. This is a single centre, non-blinded pilot randomized controlled trial at a tertiary surgical centre. Patients undergoing elective non-colorectal surgery via a midline laparotomy were randomized to EDA or CWI. Endpoints included recruitment, feasibility of assessing postoperative mobility with a pedometer and morbidity. No primary endpoint was defined and all analyses were explorative. Interventions: CWI with local anaesthetics (experimental group) vs. thoracic EDA (control). Results: Of 846 patients screened within 14 months, 71 were randomized and 62 (31 per group) included in the intention-to-treat analysis. Mobility was assessed in 44 of 62 patients and revealed no differences within the first 3 postoperative days. Overall morbidity did not differ between the two groups (measured via the comprehensive complication index). Median pain scores at rest were comparable between the two groups, while EDA was superior in pain treatment during movement on the first, but not on the second and third postoperative day. Duration of preoperative induction of anaesthesia was shorter with CWI than with EDA. Of 17 serious adverse events, 3 were potentially related to EDA, while none was related to CWI. Conclusion: This trial confirmed the feasibility of a randomized trial design to compare CWI and EDA regarding morbidity. Improvements in the education and training of team members are necessary to improve recruitment. Trial registration: DRKS00008023.